1990
DOI: 10.1111/j.1469-8137.1990.tb00444.x
|View full text |Cite
|
Sign up to set email alerts
|

An ozone‐low temperature interaction in loblolly pine (Pinus taeda L.)

Abstract: SUMMARYLoblolly pine {Pinus taeda L.) seedlings from two families differing in ozone sensitivity, were exposed to ozone and acidic precipitation in modified open-top chambers, beginning in May of 1988. Visible injury (bleached needle tips) occurred after a late-season frost in April, 1989 on newly emerging (length < 5 cm) needles. After one week, needle tips turned brown and necrotic. Incidence of injury was recorded in April, May and June, 1989. Injury only occurred on trees exposed to ozone at above-ambient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Evidence of starch accumulation and subsequent crushing of phloem cells (Wellburn & Wellburn, 1994) is consistent with reports that ozone restricts phloem loading, and, thus, assimilate translocation, from shoots to roots (Okano et al, 1984). The outcome is a change in balance between root and shoot growth, leading to reduced root : shoot ratios and potential predisposition of ozone exposed trees to drought (Mansfield, 1988;Davidson et al, 1992) and winter desiccation (Chappelka et al, 1990).…”
Section: Below-ground Processessupporting
confidence: 81%
See 1 more Smart Citation
“…Evidence of starch accumulation and subsequent crushing of phloem cells (Wellburn & Wellburn, 1994) is consistent with reports that ozone restricts phloem loading, and, thus, assimilate translocation, from shoots to roots (Okano et al, 1984). The outcome is a change in balance between root and shoot growth, leading to reduced root : shoot ratios and potential predisposition of ozone exposed trees to drought (Mansfield, 1988;Davidson et al, 1992) and winter desiccation (Chappelka et al, 1990).…”
Section: Below-ground Processessupporting
confidence: 81%
“…The outcome is a change in balance between root and shoot growth, leading to reduced root : shoot ratios and potential predisposition of ozone exposed trees to drought (Mansfield, 1988; Davidson et al. , 1992) and winter desiccation (Chappelka et al. , 1990).…”
Section: Scaling From Seedling To Tree Evidence From a Quercus Rmentioning
confidence: 99%
“…They termed them ' memory effects ' or carry-over effects which can remain latent and might take a whole season and the accompanying complimentary changes in biochemistry, together with environmental triggers to activate. There are reports of conifers which have received controlled summer O $ exposures exhibiting more winter damage in the presence of natural frosts (Brown, Roberts & Blank, 1987 ;Chappelka et al, 1990). However, in some of these studies the implication is that O $ exposure does exacerbate winter damage but via increased sensitivity to winter desiccation and\or photoinhibition rather than through a reduction in freezing tolerance (Barnes & Davison, 1988 ;Lucas & Penuelas, 1990 ;Chappelka et al, 1990).…”
Section:      mentioning
confidence: 99%
“…There are reports of conifers which have received controlled summer O $ exposures exhibiting more winter damage in the presence of natural frosts (Brown, Roberts & Blank, 1987 ;Chappelka et al, 1990). However, in some of these studies the implication is that O $ exposure does exacerbate winter damage but via increased sensitivity to winter desiccation and\or photoinhibition rather than through a reduction in freezing tolerance (Barnes & Davison, 1988 ;Lucas & Penuelas, 1990 ;Chappelka et al, 1990). Enhanced sensitivity to winter desiccation following O $ exposure might well be a consequence of restricted phloem loading and translocation of sugars to the roots (' Effects of ozone on carbon allocation ').…”
Section:      mentioning
confidence: 99%
“…Lucas et al increase the susceptibility of conifers to freezing (1988) demonstrated that loss of freezing resistance injury (Brown, Roberts & Blank, 1987; caused by ozone nnay precede any change in grow'th Lucas et al, 1988;Fincher et al, in Sitka spruce {Picea sitchensis). Furthermore, 1989;Fowler et al, 1989;Edwards, Pier & Kelly, ozone-injured tissue may exhibit reduced freezing 1990; Chappelka et al, 1990, but see Senser, 1990). resistance up to 72 d after pollution concentrations This interaction between air pollutants and frost have declined to trace levels.…”
Section: Introductionmentioning
confidence: 99%